Determinants of adoption and intensity of use of balance nutrient management systems technologies in the northern Guinea savanna of Nigeria - Akinola, Adebayo A.; Alene, Arega D.; Adeyemo, R.; Sanogo, D.; Olanrewaju, A.S.; Nwoke, C.; Nziguheba, Generose (2010)
As part of a major effort to address soil fertility decline in West Africa, an integrated soil fertility management project promoted two technology packages: a combined application of inorganic fertilizer and manure (BNMS-manure) and a soybean/maize rotation practice (BNMS-rotation) in the northern Guinea savanna (NGS) of Nigeria. This study used a tobit regression model to examine factors that influence the adoption and intensity of use of the technologies. Empirical results showed that within five years of introduction, the adoption of BNMS-rotation had reached 40% while that of BNMS-manure had reached 48%. In terms of land area, BNMS-manure occupied 35% and BNMS-rotation covered 12% of the total maize land in the zone. Factors such as access to credit, farmers’ perception of the state of land degradation, and assets ownership were the significant determinant factors of BNMS-manure, whereas offfarm income was found to be significant in determining farmers’ adoption decisions on BNMS-rotation.